2013
DOI: 10.1371/journal.pone.0075612
|View full text |Cite|
|
Sign up to set email alerts
|

The Revolving Door Phenomenon Revisited: Time to Readmission in 17’415 Patients with 37’697 Hospitalisations at a German Psychiatric Hospital

Abstract: ObjectiveDespite the recurring nature of the disease process in many psychiatric patients, individual careers and time to readmission rarely have been analysed by statistical models that incorporate sequence and velocity of recurrent hospitalisations. This study aims at comparing four statistical models specifically designed for recurrent event history analysis and evaluating the potential impact of predictor variables from different sources (patient, treatment process, social environment).MethodThe so called … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 47 publications
2
62
0
5
Order By: Relevance
“…In four studies (15.3%), men presented higher rates and a greater trend towards readmission (Batalla et al, 2013;Castro et al, 2010;Lin et al, 2010;Pfiffner et al, 2014). On the other hand, being a woman appeared as a risk factor in five other studies (Byrne et al, 2010;Callaly et al, 2011;Frick et al, 2013;Kroken et al, 2012;Sánchez et al, 2013).…”
Section: Sociodemographic and Psychosocial Datamentioning
confidence: 93%
See 2 more Smart Citations
“…In four studies (15.3%), men presented higher rates and a greater trend towards readmission (Batalla et al, 2013;Castro et al, 2010;Lin et al, 2010;Pfiffner et al, 2014). On the other hand, being a woman appeared as a risk factor in five other studies (Byrne et al, 2010;Callaly et al, 2011;Frick et al, 2013;Kroken et al, 2012;Sánchez et al, 2013).…”
Section: Sociodemographic and Psychosocial Datamentioning
confidence: 93%
“…Three articles (11.5%) showed an association between lower income and higher number of readmissions (Jaramillo-Gonzalez et al, 2014;Lin et al, 2010;Sánchez et al, 2013) and one study found no association (Kikuchi et al, 2013). Where education is concerned, in the sample profiles, most participants had a low education level (Batalla et al, 2013;Castro et al, 2010;Dahlan et al, 2013;Frick et al, 2013;Pfiffner et al, 2014;Zhang et al, 2011). One study found a significant increase in readmissions in people with high education levels (Jaramillo-Gonzalez et al, 2014) and, in three studies, education was not a significant variable (Kikuchi et al, 2013;Lin et al, 2010;Moss et al, 2014).…”
Section: Sociodemographic and Psychosocial Datamentioning
confidence: 97%
See 1 more Smart Citation
“…It is expected that PWP-GT can be a proper means of modeling the hot or cold status of a topic as PWP-GT considers that the subsequent event is conditional on the prior event [60]. The PWP-GT model is widely used in epidemiology, business, and medicine for analyzing the time gap of recurrent events [61][62][63][64].…”
Section: Survival Analysis and Topic Emergencementioning
confidence: 99%
“…Psychiatric disease does not only exhibit subjective symptomatology, but also includes functional disturbances, disability and social disadvantage [3]- [5]. Characteristics of psychiatric diseases are that the progression and remission repeatedly occur and the disease becomes chronic [6] forcing psychiatric patients to continually stay in hospitals rather than live in their communities [7] [8].…”
Section: Introductionmentioning
confidence: 99%